Justification for the physiological isolation of the torus based on the pain sensitivity of the oral mucosa - Alijon Sobirov; Sunnatullo Gafforov; Nurmukhamet Ruzuddinov; Raykhon Pulatova; Ravshanbek Jambilov; Kalamkas Ruzuddinova; Zukhriddin Djumaev; Sevara Gafforova (BIO Web of Conferences)
At the current stage of scientific and practical dental development, many patients cannot use removable dentures fully. However, there are many new effective methods for this type of orthopedic dental treatment. We are improving the methods of manufacturing high-quality removable dentures through clinical, functional, and physicomechanical research. Orthopedic dental treatment was performed in 33 patients, for whom dentures were made depending on the pain sensitivity of the torus with a certain thickness of insulation. Measurements of pain sensitivity and compliance of the oral mucosa were performed, and diagnostic models were studied. Patients who had partial and full removable plate prostheses made using our developed techniques noted a positive shift in the quality of life after prosthetics, in comparison with prostheses made earlier. The results showed that after orthopedic dental treatment, the proportion of patients who considered their quality of life to be good increased significantly (78.4%), with the initial indicator (8.1%). In addition, 16.2% of patients considered their quality of life to be satisfactory, and only 5.4% continued to consider their quality of life to be unsatisfactory, although before prosthetics, this indicator was (5.1%). These data show that high-quality dental prosthetics improve the quality of life of our patients since this indicator changed for the better from 8.1% to 78.4%. Diagnostic measures using devices for determining the pain sensitivity of the oral mucosa, the clinical and functional classification of the torus, and recommended methods of its isolation solve the problem of improving the quality of removable prostheses.